Gut microbiota and sepsis and sepsis-related death: a Mendelian randomization investigation - Shang, Weifeng; Zhang, Sheng; Qian, Hang; Huang, Sisi; Li, Hui; Liu, Jiao; Chen, Dechang (Frontiers in immunology, 2024)
It is unclear what the causal relationship is between the gut microbiota and sepsis. Therefore, we employed Mendelian randomization (MR) to determine whether a causal link exists between the two. This study used publicly available genome-wide association studies (GWAS) summary data of gut microbiota, sepsis, sepsis (critical care), and sepsis (28-day death in critical care) to perform a two-sample MR analysis. To ensure the robustness of the results, we also conducted a sensitivity analysis. For sepsis susceptibility, inverse variance weighted (IVW) estimates revealed that (OR = 0.86, 95% CI, 0.78-0.94, = 0.0017) was protective against sepsis, while (OR = 0.89, 95% CI, 0.80-0.99), (OR = 1.37, 95% CI, 1.08-1.73), (OR = 1.21, 95% CI, 1.04-1.40), (OR = 1.10, 95% CI, 1.01-1.20), (OR = 0.85, 95% CI, 0.74-0.97), and (OR = 0.81, 95% CI, 0.69-0.94) presented a suggestive association with the development of sepsis (all < 0.05). For sepsis (critical care), IVW estimates indicated that (OR = 0.70, 95% CI, 0.53-0.93), (OR = 0.67, 95% CI, 0.50-0.91), (OR = 0.49, 95% CI, 0.31-0.76), (OR = 0.51, 95% CI, 0.34-0.77), and (OR = 0.66, 95% CI, 0.44-0.99) showed a suggestive negative correlation with sepsis (critical care) (all < 0.05). For sepsis (28-day death in critical care), IVW estimates suggested that four bacterial taxa had a normally significant negative correlation with the risk of sepsis-related death, including (OR = 0.54, 95% CI, 0.30-0.95), (OR = 0.34, 95% CI, 0.14-0.83), (OR = 0.43, 95% CI, 0.22-0.83), and (OR = 0.45, 95% CI, 0.21-0.97), while two bacterial taxa were normally significantly positively linked to the risk of sepsis-related death, namely, (OR = 2.03, 95% CI, 1.01-4.08) and (OR = 2.65, 95% CI, 1.18-5.96) (all < 0.05). The robustness of the above correlations was verified by additional sensitivity analyses. This MR research found that several gut microbiota taxa were causally linked to the risk of sepsis, sepsis in critical care, and sepsis-related 28-day mortality in critical care.